Histone Acetyltransferase Cofactor Trrap Maintains Self‐Renewal and Restricts Differentiation of Embryonic Stem Cells123. (24th April 2013) - Sawan, Carla; Hernandez‐Vargas, Hector; Murr, Rabih; Lopez, Fabrice; Vaissière, Thomas; Ghantous, Akram Y.; Cuenin, Cyrille; Imbert, Jean; Wang, Zhao‐Qi; Ren, Bing; Herceg, Zdenko
Abstract Chromatin states are believed to play a key role in distinct patterns of gene expression essential for self‐renewal and pluripotency of embryonic stem cells (ESCs); however, the genes governing the establishment and propagation of the chromatin signature characteristic of pluripotent cells are poorly understood. Here, we show that conditional deletion of the histone acetyltransferase cofactor Trrap in mouse ESCs triggers unscheduled differentiation associated with loss of histone acetylation, condensation of chromatin into distinct foci (heterochromatization), and uncoupling of H3K4 dimethylation and H3K27 trimethylation. Trrap loss results in downregulation of stemness master genes Nanog, Oct4, and Sox2 and marked upregulation of specific differentiation markers from the three germ layers. Chromatin immunoprecipitation‐sequencing analysis of genome‐wide binding revealed a significant overlap between Oct4 and Trrap binding in ESCs but not in differentiated mouse embryonic fibroblasts, further supporting a functional interaction between Trrap and Oct4 in the maintenance of stemness. Remarkably, failure to downregulate Trrap prevents differentiation of ESCs, suggesting that downregulation of Trrap may be a critical step guiding transcriptional reprogramming and differentiation of ESCs. These findings establish Trrap as a critical part of the mechanism that restricts differentiation and promotes the maintenance of key features of ESCs. STEM CELLS 2013;31:979–991